2022
DOI: 10.3389/fpubh.2022.851553
|View full text |Cite
|
Sign up to set email alerts
|

Towards Integrated Air Pollution Monitoring and Health Impact Assessment Using Federated Learning: A Systematic Review

Abstract: Environmental issues such as environmental pollutions and climate change are the impacts of globalization and become debatable issues among academics and industry key players. One of the environmental issues which is air pollution has been catching attention among industrialists, researchers, and communities around the world. However, it has always neglected until the impacts on human health become worse, and at times, irreversible. Human exposure to air pollutant such as particulate matters, sulfur dioxide, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 114 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…DL is an important subset of AI and a subset of ML that demonstrates how machines can mimic humans in learning certain types of information and accumulating situational awareness ( Akhtar et al, 2023 ; Brownlee, 2017 ; Huang et al, 2023 ; Mehrjardi et al, 2023 ; Rastall & Green, 2022 ; Tanveer et al, 2023 ; Usuga-Cadavid et al, 2022 ; Velichko et al, 2023 ; Zhao et al, 2020a ; Zhou et al, 2023 ). DL techniques such as long short-term memory (LSTM), deep neural network (DNN), and other DL architectures were used ( Neo et al, 2022 ). DNNs are formed by stacking these layered networks ( Brownlee, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DL is an important subset of AI and a subset of ML that demonstrates how machines can mimic humans in learning certain types of information and accumulating situational awareness ( Akhtar et al, 2023 ; Brownlee, 2017 ; Huang et al, 2023 ; Mehrjardi et al, 2023 ; Rastall & Green, 2022 ; Tanveer et al, 2023 ; Usuga-Cadavid et al, 2022 ; Velichko et al, 2023 ; Zhao et al, 2020a ; Zhou et al, 2023 ). DL techniques such as long short-term memory (LSTM), deep neural network (DNN), and other DL architectures were used ( Neo et al, 2022 ). DNNs are formed by stacking these layered networks ( Brownlee, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unsupervised learning is typically applied to clustering issues and looks for hidden patterns or intrinsic structures in the input data ( Abd-Elrazek et al, 2021 ). ML techniques such as naive Bayes, random forest, support vector machine (SVM), decision tree, and regression models are the most widely used AI approaches ( Khairuddin et al, 2022 , 2023 ; Neo et al, 2022 ), artificial neural network (ANN), and decision trees ( Hosamo et al, 2022 ) and ML is also used for Autoregressive Integrated Moving Average (ARIMA) ( Yang et al, 2021 ). From the review, 19 studies use ML approaches for PdM using DT ( Altun & Tavli, 2019 ; Avornu et al, 2022 ; Das et al, 2021 ; Harries et al, 2023 ; Heim et al, 2020 ; Hosamo et al, 2022 , 2023 ; Hu et al, 2023a ; Luo et al, 2020 ; Mourtzis, Tsoubou & Angelopoulos, 2023 ; Mubarak et al, 2022 ; Panagou et al, 2022a , 2022b ; Rajesh et al, 2019 ; Rossini et al, 2020 ; Siddiqui, Kahandawa & Hewawasam, 2023 ; Singh et al, 2023 ; Wang et al, 2022 ; Werner, Zimmermann & Lentes, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…A review from Neo, E.X., et al [55] imposes a framework on the basis of data from environmental, health, and AQI prediction for integrated environmental and health impact assessment systems, as well as big data learning and prediction abilities of AI and FL. In the framework of early health care service preparedness prediction and hospital administration, it is also crucial for efficient medical services.…”
Section: Federated Learning In Aqi Predictionmentioning
confidence: 99%
“…The study indicated that the effect is adversely impacted by the quality of air surrounding us, and therefore having clean air is very important in extending the life span. The low quality of air has led to several health complications such as respiratory diseases, cardiorespiratory diseases, various types of cancers, and pregnancy and birth complications ( Neo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%